JURIDICAL STUDY OF LEASING OF HOSPITAL FOUNDATION ASSETS TO HOSPITALS IN THE FORM OF A LIMITED LIABILITY COMPANY - Setiyowati Setiyowati (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
Law number 28 of 2004 amendments to law number 16 of 2001 concerning foundations, in article 5 paragraph (1) explains that the assets of foundations are stopped or distributed directly or indirectly. In fact, there is a hospital from a foundation which, due to being pressured by the need to improve hospital management, the foundation which manages the hospital business unit forms a pt to manage the hospital business unit. This research discusses the role of a notary in the process of transferring assets from a hospital foundation to a hospital in the form of a limited liability company and what is the mechanism for the process of transferring assets from a hospital foundation to a hospital in the form of a limited liability company and what are the responsibilities of legal organ foundations in an effort to transfer the assets of a hospital foundation hospital to a hospital in the form of a limited liability company. This research is a normative juridical research with an approach based on the main legal material by examining the theories, concepts, legal principles and laws and regulations related to research. The results of the analysis are presented qualitatively. Data in the field was taken through interviews with the foundation and notary who made the lease deed. The results of this study are the role of the notary in the transfer of assets, namely the role of the notary as the maker of the land lease agreement owned by pt husada to khoirunissa hospital. The mechanism for the process of transferring assets from a hospital foundation to a hospital in the form of a pt is through a lease agreement. PT. Husada leases its assets in the form of land and is leased by the khoirunisa foundation on which a foundation hospital is built called rsia umi barokah.